Monounsaturated 14:1n‐9 and 16:1n‐9 Fatty Acids but not 18:1n‐9 Induce Apoptosis and Necrosis in Murine HL‐1 Cardiomyocytes. Issue 1 (27th November 2013) - Hoffmann, Lars; Seibt, Annette; Herebian, Diran; Spiekerkoetter, Ute
Abstract: Patients with inborn errors of long‐chain fatty acid oxidation accumulate disease‐specific acylcarnitines and triacylglycerols in various tissues. Some of these patients present significant cardiac diseases such as arrhythmias and cardiomyopathy. The mechanism of how fatty acid accumulation is involved in disease pathogenesis is still unclear but apoptosis of cardiomyocytes has been suggested to be one possible mechanism of cardiomyopathy development. In this study, we measured lipid uptake and intracellular lipid accumulation after incubation of HL1 cardiomyocytes with different saturated and monounsaturated long‐ and medium‐chain fatty acid species for various time periods and at different physiological concentrations. We assessed apoptosis induction by analyzing the mitochondrial membrane potential and TLR‐4 expression as well as the composition of the accumulating triacylglycerols. We identified only 14:1 and 16:1 monounsaturated fatty acids potentially leading to an increase in TLR‐4 expression and disruption of the mitochondrial membrane potential, resulting in apoptosis and necrosis in cultured cardiomyocytes. This study demonstrates significant toxicity of especially those fatty acid species in vitro that significantly accumulate in fatty acid oxidation defects presenting with cardiac disease such as very long‐chain acyl‐CoA dehydrogenase, carnitine acylcarnitine translocase and carnitine palmitoyl‐CoA transferase deficiencies.